Immunological features protect against candida spp. - Spolidorio, Denise M. Palomari; Francisconi, Renata Serignoli; Spolidorio, Luís Carlos [UNESP]; Rosa, Edvaldo Antonio Ribeiro (Springer Nature, 2015)
The epithelial mucosa is an important component of the host immune defense and immune surveillance since it is the first layer that most microorganisms initially contact. The most important function of the immune system is to discriminate between self and nonself, a property that is essential for the maintenance of immune homeostasis. This specialized interaction results in passive coexistence of microorganisms with host, as in the case of commensal microorganisms, or a breach of the mucosa barrier and subsequent cell injury, as occurs during infection with microbial pathogens.